Creditors' Decisions to Waive Violations of Accounting-Based Debt Covenants - Kevin C. W. Chen; K. C. John Wei (The Accounting Review, 1993)
[Positive theory hypothesizes that accounting-based debt covenants are important factors in accounting choices. According to Watts and Zimmerman's (1990) survey, this hypothesis has generally been supported by earlier studies. That is, the closer the firm is to violating accounting covenants, the more likely managers would choose income-increasing methods. Recently, research attention has shifted to the event of covenant violation itself. For example, Beneish and Press (1993) estimate debtors' costs of violations. Further, DeFond and Jiambalvo (1991) and Sweeney (1992) examine debtors' manipulative behavior before covenant violations. These latter studies find that violations of accounting covenants are costly to debtors, who generally try to manipulate accounting numbers to avoid or defer technical defaults. The present study also focuses on the event of violation, but from the perspective of creditors. It explains two aspects of creditors' decision process following covenant violations. First, we find that creditors react to actual violations in two distinct ways: they could either waive the violations or could demand certain conditions such as early payment, increase of interest rate, reduction of borrowing base, and so forth. Second, we also model creditors' decisions either to waive or to call the debt using the option-pricing framework. We hypothesize that the determinants of waiver decisions include the firm's bankruptcy probability and leverage ratio. Moreover, maturity, size, and security of the debt issue involved should also be important factors in the waiver decisions. Empirically, we find that creditors are more likely to grant a waiver to the firm with a lower estimated probability of bankruptcy and a lower leverage ratio. Further, debt issues that are secured or smaller in size are more likely to have violations waived than unsecured or larger issues. The maturity variable, however, is not found a significant determinant of the waiver decisions. Using the factors identified in this study, managers can assess the probability of receiving a waiver and prepare necessary strategies to ensure the firm's survival. Auditors also can use those factors to assess the possibility of the client's receiving a waiver of covenant violation as part of their evaluation of the firm's ability to continue as a going concern. Moreover, since debtors prefer waivers to nonwaivers, the prospect of receiving a waiver is likely to influence managerial behavior, including the choice of accounting alternatives. Managers expecting a nonwaiver from creditors would have more incentive to select accounting methods to avoid covenant violations.]